Load distribution of planetary roller screw mechanism and its improvement approach. (November 2016) - Zhang, Wenjie; Liu, Geng; Tong, Ruiting; Ma, Shangjun
A model of load distribution over threads of planetary roller screw mechanism (PRSM) is developed according to the relationships of deformation compatibility and force equilibrium. In order to make the applied load of PRSM uniformly distributed over threads, an improvement approach is proposed, in which the parameters of thread form of roller and nut are redesigned, and the contact conditions of roller with screw and nut are changed to compensate the axial accumulative deformation of shaft sections of screw and nut. A typical planetary roller screw mechanism is taken as example to analyze the load distribution, and the effects of installation configurations, load conditions and thread form parameters on load distribution are studied. Furthermore, the improvement approach is applied to the PRSM, and it is proved to be beneficial to reach uniform load distribution over threads.